The ‘Sound’ medium Akashvani the Kisan Vani - Pulugurta Chandra Sekhar (Journal of Advanced Research in Journalism & Mass Communication, 2021)
All India Radio (AIR), popularly known as Akashvani since 1957. AIR was made a separate department under Prasara Bharati Corporation of the Ministry of Information and Broadcasting. Communication by word of mouth alone had been possible until radio was used to spread the word. Radio has been the most important and the most effective medium for providing information and stimulating new attitudes wherever it has reached. Radio is an amazingly effective medium, popular, pleasing, even exciting. It is hardly possible to exaggerate the role which radio can play in our society with seventy percent of our people illiterate and with most of them living in rural areas. Radio has been the most important and the most effective medium for providing information and stimulating new attitudes wherever it has reached. Hence, Radio is called people friendly medium, particularly in rural areas it is farmer friendly medium. Indeed, Radio is a ‘Sound’ medium. How to cite this article: Sekhar PC. The ‘Sound’ Medium Akashvani the Kisan Vani. J Adv Res Jrnl Mass Comm 2020; 7(3): 21-24.